Nutritive value of juazeiro (Zizyphus joazeiro) hay for sheep and goats - Barros, Nelson Nogueira; Freire, Luiz Carlos Lopes; Lopes, Expedito Aguiar; Johnson, William Lawrence (Pesquisa Agropecuaria Brasileira, 1991)
Six sheep of the Santa Inês genotype and six goats of undefined genotype (SRD) were used to evaluate the nutritive value of "juazeiro" hay (Zizyphus joazeiro). Experimental animals were kept in elevated metabolism crates for a 14-day adaptation period followed by a 7-day collection period of total feces and urine. Sheep and goats were adult castrated males. They were given ad libitum access to forage consumption, water and mineralized salt. Crude protein, neutral detergent fiber, hemicellulose and KMnO4 lignin contents of the hay were 15.2, 66.7, 24.8 and 14.2%, respectively. There was no significant difference between animal species for any of these variables. Consumption of dry matter, apparent digestibility coefficient of dry matter and nitrogen balance were 76.6 and 87.1 g/kg0.75/day, 43.7 and 39.9% and 6.7 and 6.0 g/day for goats and sheep, respectively. The results indicated that "juazeiro" leaves can be used as feed by sheep and goats, as an alternative food source during the dry season.